Antibacterial activity of three wild wood-decaying fungi in southern Vietnam toward Vibrio parahaemolyticus bacterium in aquaculture wastewater - Vu, Ngo Nguyen; Ngoc, Pham Van Kim; Hoa, Pham Thi (Vietnam Journal of Biotechnology, 2018)
This research demonstrated antibacterial activity of wood-decaying fungi to treat the aquaculture pathogenic bacterium, Vibrio parahaemolyticus (V. parahaemolyticus). Three wild wood-decaying fungi (WDF) collected in Southern Vietnam including Flavodon flavus (F. flavus), Physisporinus vitreis (P. vitreis), and Schizophyllum commune (S. commune) were tested to treat V. parahaemolyticus presented in aquaculture wastewater. Fungal adaptation to different salt concentrations at 0, 10, 15, 20, and 30‰ was tested for the assessment of application potential of these fungi in the aquaculture farming. Fungal mycelium could adapt differently to saline conditions. All three strains grew well at low salt concentration (0-10‰), but only F. flavus survived up to 20‰ NaCl. For the antibacterial ability toward V. parahaemolyticus, two experiments using mycelium culture broth and mycofiltration were performed. Results revealed that all the three species of WDF effectively inhibited V. parahaemolyticus. Thus, mycelium culture broth of P. vitreis, S. commune, and F. flavus could inhibit 98.7, 96.5 and 97.8% V. parahaemolyticus, respectively after 8 hours. Even higher inhibitory effects were observed in the mycofiltration experiment, the efficiency reached 100% for P. vitreis, and 98% for F. flavus and S. commune after 8 hours. The obtained results showed very good application potential of myco-remediation technique using WDF in the treatment of V. parahaemolyticus in aquaculture farming. Mycofilter can be used as a new approach for controlling aquaculture disease, specifically Vibrio sp. treatment based on the antibiotic capability of these WDF. The reduction in pH of the mycelium broth can illustrated for the acidification during the mycelium development and could link with the bactericide capacity of these WDF.